An effective aeration system for high performance pond aeration at low energy cost - Aytac, Ayca; Kelestemur, Guluzar Tuna; Tuna, M. Cihat (Springer, 2024)
With the effective use of aerators with low energy cost and high aeration performance, aquaculture areas can be developed and supported. The main objective of this study is to determine the optimal physical parameters of high aeration capacity high head conduits and to ensure low energy costs, thus to present a comprehensive review of its usability for pond aeration. In this study, a high-head gated conduit was used as the aeration unit. After obtaining the design that will maximize the aeration performance of the high-head gated conduit, a prototype model was developed to ensure its effective use in pond aeration. The parameters affecting the performance of this developed aeration system and the corresponding energy cost values were determined. According to the results, the most important parameters affecting the aeration performance are, respectively, flow rate, the opening of the gate, hydrostatic level, and jet plunge angle. In the optimal design, more than three times the unit volume of water circulating in the system is added to the system. The cost value of this operation in terms of energy was measured as 0.10 kWh/m3 air. The developed system was found to have significantly higher energy efficiency values compared to alternatives, based on specific energy consumption data.
Keywords: Aeration cost; Aquaculture; Pond aeration-conduit